skills mismatch and inadequacy education-job -analytical study of previous studies- - Fatma Maamri; Lassassi Moundir; Weam El khoujah (Journal of North African Economies, 2025)
The emergence of the theory of human capital in the late sixties of the last century in the United States of America contributed to the expansion of higher education, but the results of this were the emergence of a defect in the labor market represented in the imbalance of the relationship with work education, which took different forms, and the continuation of the phenomenon for a long time contributed to the spread of unemployment. Through our research paper, we will address the topic of the imbalance of the education-work relationship within a theoretical context, in an attempt to identify what it is as one of the new topics that fall within the economics of labor, which is concerned with determining the productivity of individuals, and we have relied on the descriptive analytical approach of previous studies that have already dealt with the subject from different perspectives.